Upaya Meningkatkan Aktivitas dan Hasil Bimbingan Konseling Pada Siswa Kelas X SMA Negeri 1 Morotai Melalui Penerapan Model Pembelajaran NHT - M. Hatta Hi. Saraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
The cornerstone of the NHT learning philosophy is the constructivist view. Students acquire knowledge as a result of the construction process that is continuously accepted. Experiences are arranged, organized and rearranged by linking the structure of the students, little by little modified and developed. The purpose of this research is to find out how to increase the activities and outcomes of Counseling Guidance for V MIN 01 students in Ternate City through the application of the NHT learning model in the teaching and learning process. This research is a type of classroom action research (CAR) that is reflective, participatory and collaborative which aims to make improvements to systems, working methods, processes, content and competencies or learning situations in the classroom. The results of this study indicate that there is an effect of the NHT model cooperative learning strategy on student learning outcomes with an average value of the first cycle (68.5%.) and the second cycle average (87.9%). Thus, it can be concluded that the NHT model can improve learning outcomes in the Indonesian language field of study in CLASS X SMA Negeri 1 Morotai students.